2014
DOI: 10.3109/01480545.2014.928721
|View full text |Cite
|
Sign up to set email alerts
|

SiO2Nanoparticule-induced size-dependent genotoxicity – anin vitrostudy using sister chromatid exchange, micronucleus and comet assay

Abstract: Fine particles with a characteristic size smaller than 100 nm (i.e. nanoparticlesspread out in nowadays life. Silicon or Si, is one of the most abundant chemical elements found on the Earth. Its oxide forms, such as silicate (SiO4) and silicon dioxide, also known as silica (SiO2), are the main constituents of sand and quartz contributing to 90% of the Earth's crust. In this work, three genotoxicity systems "sister chromatid exchange, cytokinesis block micronucleus test and single cell gel electrophoresis (come… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 46 publications
0
20
0
1
Order By: Relevance
“…Okada suggested prolonged activation of inflammatory cells generates ROS that can damage DNA and contribute to carcinogenesis in chronic inflammatory disease [28]. Besides, metal particles may induce other cellular responses that in turn lead to genotoxicity, such as causing oxidative stress, inflammation, and aberrant signaling responses [29,30]. In our study, comet assay results indicated silver particles cause significant genotoxicity in mononuclear leukocytes in silver jewelry workers (Figs.…”
Section: Discussionmentioning
confidence: 75%
“…Okada suggested prolonged activation of inflammatory cells generates ROS that can damage DNA and contribute to carcinogenesis in chronic inflammatory disease [28]. Besides, metal particles may induce other cellular responses that in turn lead to genotoxicity, such as causing oxidative stress, inflammation, and aberrant signaling responses [29,30]. In our study, comet assay results indicated silver particles cause significant genotoxicity in mononuclear leukocytes in silver jewelry workers (Figs.…”
Section: Discussionmentioning
confidence: 75%
“…Nanoparticle size seems to influence toxicity. Studies involving peripheral blood lymphocytes treated with SiO 2 nanoparticles of different sizes (6,20, and 50 nm) induced size-dependent cytotoxic, genotoxic, and mutagenic effects [54].…”
Section: Interaction Of Nanomaterials With Peripheral Mononuclear Cellsmentioning
confidence: 99%
“…Comet assay (Singh, McCoy, Tice, & Schneider, 1988) is another rapid, sensitive, and inexpensive biomarker for qualitative and quantitative evaluation of DNA damage in any accessible cells. It have been recommended as a reliable biomarker for the analysis of genotoxicity and for screening of novel cosmetics and drugs testing by the Registration, Evaluation, Authorization, and Restriction of Chemicals Substances program of the European Commission (REACH) and European Food Safety Authority (EFSA) (Azqueta & Dusinska, 2015;Battal et al, 2015;Ferraro, Anselmi-Tamburini, Tredici, Ricci, & Sommi, 2016;Speit & Rothfuss, 2012). In this assay, a damaged cell visualized as a comet, with distinct head and tail regions.…”
Section: Introductionmentioning
confidence: 99%